2020
DOI: 10.2147/oajc.s250462
|View full text |Cite
|
Sign up to set email alerts
|

<p>Married Women’s Decision-Making Power in Family Planning Use and its Determinants in Basoliben, Northwest Ethiopia</p>

Abstract: Background: Women's decision-making power influences the use of family planning. It is one of the denied fundamental rights of women, particularly in developing countries. Objective: This study was aimed to assess married women's decision-making power in the use of family planning and its associated factors among married reproductive age women in Basoliben, Amhara, Ethiopia, 2018. Methods: A community-based cross-sectional study was conducted among married reproductive age women from March 1 to 30, 2018. A mul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
8
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 28 publications
4
24
8
1
Order By: Relevance
“…On the other hand, in this study we also observed that women whose husbands' had high desire number of children had poor decision making power to use FP. This nding was similar to a study conducted in Hondurans (44) and Ethiopia (28). This could be related to husbands might in uence women not to use FP especially in developing countries.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…On the other hand, in this study we also observed that women whose husbands' had high desire number of children had poor decision making power to use FP. This nding was similar to a study conducted in Hondurans (44) and Ethiopia (28). This could be related to husbands might in uence women not to use FP especially in developing countries.…”
Section: Discussionsupporting
confidence: 89%
“…However, decisions for contraceptive use may be affected by unbalanced power relations between women and their partners, especially in more malecontrolled societies and cultural discrimination (20). Furthermore, previous studies showed that decisionmaking power of women to use family planning was associated with education (4,(21)(22)(23), age (4,(23)(24)(25)(26), better knowledge (24,27,28), working status of women (25,26,29), gender equitable attitude (27), number of living children (21,25,26), socio-economic status (22,23,(29)(30)(31), residence (25,26), husband desire number of children (28) and attitude towards family planning (24).…”
Section: Introductionmentioning
confidence: 99%
“…This might be due to married women may be likely to be having sex more regularly than unmarried women, which may explain their high post-abortion family planning utilization. Besides, currently, married women's decision-making power on family planning has been raised [61,62] and contraceptive prevalence continues to increase [63]. Similarly, multiparous women were more likely to utilize post-abortion family planning compared to their counterparts.…”
Section: Discussionmentioning
confidence: 99%
“…There is a lack of nationally representative data on women's decision-making on family planning use [10,11]. Moreover, there are studies conducted in different parts of the country on women's decision-making in family planning [14,15,[21][22][23][24][25]. However, there are inconsistent ndings on prevalence and its determinants women's decision-making on family planning use.…”
Section: Introductionmentioning
confidence: 99%